Advantages of using technology to assess speaking skills. - Realpe Merchán, Anggy Xiomara (2024)
The present research is focused on a study of the use of technological tools to assess speaking skills; the integration of technology in educational assessment enhances engagement, diverse assessment formats, timely feedback, efficiency, and equity. The objective of this study is to explore and analyze the advantages of these tools to assess speaking skills. The research was carried out through a qualitative methodology, which allowed the description of experiences and perceptions of educators applying technology to assess speaking skills. The data was collected through one-on-one interviews. The findings suggest that technology offers numerous advantages for assessing speaking skills, it increases student engagement and reduces anxiety by creating dynamic, multimedia-rich environments. Technology’s flexibility and accessibility accommodate diverse learning styles and schedules, supporting personalized language education experiences.